Characterizing the Longitudinal Patterns of Substance Use Among Individuals Diagnosed with Serious Mental Illness after Psychiatric Hospitalization - Bahorik, Amber L. (2013)
AIM: Characterize longitudinal patterns of substance use across a large sample of psychiatric patients discharged from inpatient admission, followed for 1-year post-hospitalization. DESIGN: Prospective cohort study. SETTING: Kansas City, Missouri, USA; Pittsburgh, Pennsylvania, USA; Worcester, Massachusetts, USA. PARTICIPANTS: Eight hundred one schizophrenia-spectrum (N=204), bipolar (N=137) and depressive disorder (N=460) patients from the MacArthur Violence Risk Assessment Study. MEASUREMENTS: Symptoms, functioning, drug/alcohol use assessed by the Brief Psychiatric Rating Scale, the Global Assessment of Functioning, and substance use interviews. FINDINGS: Patients used alcohol (67.0%; N=540) and cannabis (30.0%; N= 237) more frequently than other substances up to 30 days before admission, and those with depressive and schizophrenia-spectrum used heroin more than individuals with bipolar (p = .023). Post-hospitalization, patients using alcohol (B = −.15, p <.001) and cannabis (B= −.27, p <.001) decreased, but patterns varied across diagnosis and genders. Patients using cannabis decreased at greater rates in depressive and schizophrenia-spectrum compared with bipolar (all p <.05), and more men used alcohol (B = .76, p < .001) and cannabis (B = 1.56, p < .001) than women. Cannabis (B = 1.65, p < .001) and alcohol (B = 1.04, p = .002) were associated with higher symptomatology; cannabis (B = −2.33, p < .001) and alcohol (B = −1.45, p = .012) were associated with lower functioning. CONCLUSIONS: Substance use is frequent and associated with poor recovery in patients with serious mental illness recently discharged from psychiatric hospitalization. Addiction treatments personalized by diagnosis and gender may be effective for improving outcomes in people with serious mental illness.